(untitled) (Tempo e Argumento, 2024)
The article discusses the effects of Brazilian politics critical situation in the last decade on the academic production in political science and constitutional law regarding constitutional democracy, from the point of view of the destabilization of their relations with time. Its objective is to explore the implications of this change for the relationships between researches in this field and the history of the present. It explores some of the relevant works in political science and constitutional law that carry out comprehensive analyzes on the concept of the Constitution, political institutions and government politics at the national level, as well as academic and public debate intervention publications on the last decade political process. The works were chosen based on monitoring academic production in these areas and on survey and selection in digital bibliographic databases. Concretely, the article’s results inform the analysis of materials produced by ongoing research regarding the work of researchers on Brazilian constitutional democracy in the last decade. The article also aims to contribute theoretically and analytically for the field of political studies on law.